S100Z is expressed in a lateral subpopulation of olfactory receptor neurons in the main olfactory system of Xenopus laevis - Kahl, Melina; Offner, Thomas; Trendel, Alena; Weiss, Lukas; Manzini, Ivan; Hassenklöver, Thomas; Justus Liebig University Giessen (My University, 2024)
In contrast to other S100 protein members, the function of S100 calcium-binding protein Z (S100Z) remains largely uncharacterized. It is expressed in the olfactory epithelium of fish, and it is closely associated with the vomeronasal organ (VNO) in mammals. In this study, we analyzed the expression pattern of S100Z in the olfactory system of the anuran amphibian Xenopus laevis. Using immunohistochemistry in whole mount and slice preparations of the larval olfactory system, we found exclusive S100Z expression in a subpopulation of olfactory receptor neurons (ORNs) of the main olfactory epithelium (MOE). S100Z expression was not co-localized with TP63 and cytokeratin type II, ruling out basal cell and supporting cell identity. The distribution of S100Z-expressing ORNs was laterally biased, and their average number was significantly increased in the lateral half of the olfactory epithelium. The axons of S100Z-positive neurons projected exclusively into the lateral and intermediate glomerular clusters of the main olfactory bulb (OB). Even after metamorphic restructuring of the olfactory system, S100Z expression was restricted to a neuronal subpopulation of the MOE, which was then located in the newly formed middle cavity. An axonal projection into the ventro-lateral OB persisted also in postmetamorphic frogs. In summary, S100Z is exclusively associated with the main olfactory system in the amphibian Xenopus and not with the VNO as in mammals, despite the presence of a separate accessory olfactory system in both classes.
Keywords: ddc:570